Effects of cognitive training and behavior modification on aggressive behavior and sleep quality in schizophrenia - Wang, Jing; Cheng, Gangming; Li, Hongjie; Yang, Wei (Frontiers in Psychiatry, 2024)
Background: Schizophrenia (SCZ) is linked to a heightened risk of impulsive aggression and disturbances in sleep patterns. Cognitive and social cognitive impairments have been connected to aggression, with social cognitive deficits appearing to play a more immediate role. In this investigation, we conducted a retrospective analysis of the impact of cognitive training and sleep interventions on aggressive behavior and the quality of sleep among individuals with SCZ who were hospitalized. Methods: This study divided 80 hospitalized patients into two groups according to medical advice, namely the normal group and the study group. The control group received routine drug treatment and education; The research group implemented cognitive training and sleep intervention based on the normal group. Collect basic clinical data, aggressive behavior indicators, and sleep quality indicators.Results: There is no difference in the basic information statistics between the two groups. Both groups can reduce aggressive behavior and improve sleep quality. In the study group, there was a notable decrease in aggressive behavior compared to the control group. Furthermore, the sleep quality in the study group exhibited significant improvement when compared to the control group. Conclusion: Cognitive training and sleep intervention have been proven to be effective nonpharmacological treatments, effectively reducing aggressive behavior and improving sleep quality.